2020
DOI: 10.1016/j.phanu.2020.100228
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of methotrexate efficacy by green tea polyphenols in rat adjuvant arthritis

Abstract: Highlights-Co-administration of green tea extract and methotrexate (MTX) has been studied in arthritic rats-A green tea extract gradually decreased the effectiveness of MTX on arthritic score-A green tea extract alone and with MTX reduced MCP-1, but counteracted IL-17 only at day 14-A green tea extract inhibited iNOS mRNA and GGT, but in a less extent compared to MTX-Long-term administration of green tea extract may inhibit the therapeutic action of methotrexate 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
(55 reference statements)
1
3
0
Order By: Relevance
“…Earlier findings suggested that major clinical markers, HPV and body weight gain, are remarkably worsened due to inflammation and were effectively diminished by administration of compounds with anti-oxidative and/or anti-inflammatory properties [38][39][40]. The protective effect of MTX against AA development agrees with previously reported results [23,28,37,40,41] as well as with changes of HPV shown in Figure 3. Combination of RB with MTX did not improve these protective effect of MTX (Figures 2 and 3).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Earlier findings suggested that major clinical markers, HPV and body weight gain, are remarkably worsened due to inflammation and were effectively diminished by administration of compounds with anti-oxidative and/or anti-inflammatory properties [38][39][40]. The protective effect of MTX against AA development agrees with previously reported results [23,28,37,40,41] as well as with changes of HPV shown in Figure 3. Combination of RB with MTX did not improve these protective effect of MTX (Figures 2 and 3).…”
Section: Discussionsupporting
confidence: 88%
“…The AA is a well-established model of inflammation [20,21]. The adjuvant arthritis was induced in rats with weight of 160-180 g (6 weeks) by an individual intradermal immunization at the base of the tail with suspension of 0.1 mL of 12 mg/mL heat-inactivated MB powder suspended in incomplete IFA according to our previous protocol [22,23].…”
Section: Adjuvant Induced Arthritis In Lewis Ratsmentioning
confidence: 99%
“…Then again, this model lacks the chronic progressive nature of RA, and the pathological changes are self-limiting [ 130 ]. Adjuvant arthritis was induced in rats with a weight of 160–180 g (6 weeks) by individual intradermal immunization at the base of the tail with a suspension of 0.1 mL of 12 mg/mL heat-inactivated Mycobacterium butyricum powder suspended in incomplete Freund’s adjuvant according to our previous protocol [ 131 , 132 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that EGCG negatively regulates signal transduction pathways and plays an important role in arthritis and joint injury (Khan et al, 2008). In the rat model of human rheumatoid arthritis established by Ponist, it was found that the plasma monocyte chemoattractant protein-1 (MCP-1) level was significantly decreased on the 14th day after the administration of TPs (Ponist et al, 2020).…”
Section: Anti-inflammationmentioning
confidence: 99%